Antibiotic resistance of enterobacteria isolated from monkeys (Ateles, Callicebus and Lagothrix) in semi-captivity in a rescue centre, Peru - Medina G., Claudia (2017)
Several genera and species of nonhuman primates can be found in Peru. Among them, Ateles belzebuth, Ateles chamek, Callicebus oenanthe, Lagothrix cana and Lagothrix lagotricha. These species according to the IUCN Red List are in the threatened category. The aim of this study was to determine the antibacterial sensitivity profile of enteric isolates from Ateles, Callicebus and Lagothrix raised in semi-captivity. Sampling was performed by rectal swab in 56 nonhuman primates in the Center for Rescue and Rehabilitation of Primates Ikama Peru. Isolation and bacterial identification was performed using a standard protocol and bacterial sensibility by the Kirby-Bauer technique. A total of 106 bacterial strains of the family Enterobacteriaceae were isolated, where the most prevalent species was Escherichia coli (45.5%, 45/106). The isolates showed greater resistance to cephalothin (46.2%), amoxicillin - clavulanate (31.1%), tobramycin (30.2%) and tetracycline (24.5%).